A copper adsorption material, a preparation method and application thereof

CN122647665APending Publication Date: 2026-08-28JIANGXI WULI ZENGZHI RECYCLING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610806381.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

吸附法因操作简便、能耗低、无二次污染等优势受到广泛关注,但现有铜吸附材料普遍存在吸附动力学慢、选择性不足、抗干扰能力差、循环稳定性不佳等问题

Benefits of technology

1.本发明以水杨酰肼类单体为功能单体通过乳液聚合制得铜吸附材料,其对Cu2+具有超高的选择性,选择性系数最高达187,远高于常规吸附材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122647665A_ABST
    Figure CN122647665A_ABST
Patent Text Reader

Abstract

The application provides a copper adsorption material and a preparation method and application thereof, and the copper adsorption material is prepared by using salicylic hydrazide monomers and methacrylic acid as raw materials through an emulsion polymerization method. The salicylic hydrazide monomers used in the application are salicylic hydrazide derivatives with introduced propylene bonds, and the multi-dentate coordination structure of the salicylic hydrazide derivatives can specifically chelate copper ions; the hydrophilic monomer used is methacrylic acid, and the carboxyl group of the methacrylic acid can bring good hydrophilic performance to the material and improve adsorption kinetics. The copper adsorption material of the application is applied to a mixed solution containing copper ions, nickel ions and cobalt ions to selectively separate copper ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal ion adsorption materials technology, specifically to a copper adsorption material, its preparation method, and its application. Background Technology

[0002] With the rapid development of the new energy vehicle industry, the number of retired lithium-ion batteries has exploded. Ternary lithium batteries contain as much as 10-15% copper, and are also rich in valuable metals such as nickel and cobalt. In wet recycling processes, the acid leaching solution undergoes sulfidation precipitation treatment, producing a large amount of copper sulfide slag, typically composed of approximately 16% copper, 5% nickel, and 5% cobalt. The tiered separation and recovery of these valuable metals is both a necessity for resource recycling and a requirement for environmental protection.

[0003] However, Cu in the leaching solution of copper sulfide slag 2+ Ni 2+ Co 2+ Similar ionic radii (Cu) 2+ The ionic radius of Ni is 73 pm. 2+ The ionic radius of Co is 69 pm. 2+ The ionic radius of the two molecules is 74.5 pm, and their chemical properties are similar, making traditional separation methods face many bottlenecks.

[0004] Chemical precipitation is simple to operate but suffers from poor selectivity, severe co-precipitation, low product purity, and the generation of large amounts of secondary waste. Solvent extraction, while offering high separation efficiency, suffers from emulsification and significant solvent loss, flammable and explosive organic phases, long process flows, and high equipment investment. Adsorption methods have gained widespread attention due to their ease of operation, low energy consumption, and lack of secondary pollution; however, existing copper adsorption materials generally suffer from slow adsorption kinetics, insufficient selectivity, poor interference resistance, and unsatisfactory cycle stability. Therefore, the development of a Cu adsorption method is needed. 2+ Copper adsorbent materials, which possess high selectivity and rapid adsorption kinetics, can work effectively in complex coexisting ion systems, and are reusable, have significant industrial application value. Summary of the Invention

[0005] The technical problem to be solved by this invention is how to provide a Cu 2+ Highly selective adsorption materials.

[0006] The present invention solves the above-mentioned technical problems through the following technical means:

[0007] The first aspect of this invention provides a copper adsorbent material, which is prepared by emulsion polymerization of a salicylhydrazine monomer and methacrylic acid as raw materials; the structural formula of the salicylhydrazine monomer is as follows: R1 is one of H, N(C2H5)2, or NC4H8O, and R2 is H or CH3.

[0008] Beneficial effects: The salicylhydrazine monomer used in this invention is a salicylhydrazine derivative with an introduced propylene bond, whose multidentate coordination structure enables specific chelation with copper ions; the hydrophilic monomer used is methacrylic acid, whose carboxyl group imparts good hydrophilicity to the material and enhances adsorption kinetics. The copper adsorbent material of this invention is applied to the selective separation of copper ions in a mixed solution containing copper, nickel, and cobalt ions.

[0009] Preferably, the molar ratio of methacrylic acid to salicylhydrazine monomer is 1:0.33~1.5.

[0010] More preferably, the molar ratio of salicylhydrazide monomer to methacrylic acid is 1:1.

[0011] The second aspect of this invention includes a method for preparing the copper adsorbent material described above, comprising the following steps: S1 is obtained by mixing salicylhydrazine compounds and propylene compounds, dissolving them in chloroform, and then reacting them with a catalyst to obtain salicylhydrazine monomers. S2 involves adding salicylhydrazine monomers, methacrylic acid, crosslinking agent, and initiator to chloroform and stirring until homogeneous to form a pre-emulsion. Water containing emulsifier is then added to the pre-emulsion and stirred to form an emulsion. After deoxygenation of the emulsion, a copper adsorbent material is obtained.

[0012] Preferably, the salicylhydrazide compounds include one or more of 2-hydroxybenzoylhydrazide, 2-hydroxy-4-diethylaminobenzoylhydrazide, and 2-hydroxy-4-morpholinobenzoylhydrazide.

[0013] Preferably, the propylene compounds include one or more of methacryloyl chloride, methacrylic anhydride, acryloyl chloride, and acrylic anhydride.

[0014] Preferably, the molar ratio of salicylhydrazine compounds to propylene compounds is 1:0.9~1.2.

[0015] More preferably, the catalyst is triethylamine, and the amount of triethylamine added is 0.9 to 1.1 times the molar number of the salicylhydrazine compound.

[0016] More preferably, in S1, the reaction is carried out at room temperature for 4 to 8 hours.

[0017] More preferably, in S1, after the reaction is completed, the mixture is cooled to room temperature, filtered, washed, recrystallized, and dried under vacuum to obtain a salicylhydrazine monomer.

[0018] Preferably, the crosslinking agent is ethylene glycol dimethacrylate, and the ethylene glycol dimethacrylate is 0.5 to 5% of the molar amount of salicylhydrazine monomer.

[0019] Preferably, the emulsifier is sodium dodecyl sulfate, which is 1 to 5% of the molar amount of salicylhydrazine monomer.

[0020] Preferably, the initiator is azobisisobutyronitrile, and the azobisisobutyronitrile is 0.2 to 2% of the molar number of the salicylhydrazine monomer.

[0021] More preferably, in S2, the reaction temperature is 70~85℃ and the reaction time is 4~10h.

[0022] More preferably, in S2, after the reaction is completed, the product is cooled to room temperature, and then centrifuged or filtered, washed, vacuum dried and ground to obtain the copper adsorbent material.

[0023] More preferably, the vacuum drying temperature is 50~70℃ and the vacuum drying time is 12~24h.

[0024] The third aspect of the present invention provides an application of a copper adsorbent material in copper-containing wastewater, wherein the copper adsorbent material is the copper adsorbent material described above or prepared by the method described above.

[0025] More preferably, copper-containing wastewater includes one or more of the following: leaching solution of copper sulfide slag from wet recovery of waste lithium batteries, electroplating wastewater, or acidic mine drainage.

[0026] More preferably, the adsorption conditions are: the pH of the copper-containing wastewater is 4-7, the dosage of copper adsorbent material is 0.5-2 g / L, the contact time is ≥0.5 h, and the temperature is 15-45 ℃.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention uses salicylhydrazine monomers as functional monomers to prepare copper adsorbent materials via emulsion polymerization, which are effective for adsorbing Cu. 2+ It exhibits extremely high selectivity, with a selectivity coefficient as high as 187, which is far higher than that of conventional adsorbent materials.

[0028] 2. Copper adsorbents have a large adsorption capacity, with a static adsorption capacity of 186.32 mg / g and a dynamic column adsorption capacity of 139.76 mg / g, meeting the needs of industrial applications.

[0029] 3. Copper adsorbent materials have strong anti-interference ability and can withstand high salt and high organic matter environments, making them suitable for actual industrial wastewater with complex composition.

[0030] 4. The copper adsorbent material has excellent regeneration performance, with a capacity retention rate of 94.7% after 10 cycles, which reduces operating costs.

[0031] 5. The preparation method of copper adsorbent materials is simple, the conditions are mild, and it is easy to scale up, showing good prospects for industrialization. Attached Figure Description

[0032] Figure 1 This is the 1H NMR spectrum of the salicylhydrazine monomer in Example 1 of this invention; Figure 2 This is the carbon NMR spectrum of the salicylhydrazine monomer in Example 1 of this invention; Figure 3 These are FT-IR structural diagrams of the copper adsorbent materials prepared in Examples 1 and 3 of this invention; Figure 4 This is an ion selectivity diagram of the copper adsorption material in the experimental examples of this invention; Figure 5 This is the isothermal adsorption diagram of the copper adsorption material in the experimental examples of this invention; Figure 6 This is the adsorption kinetics diagram of the copper adsorbent material in the experimental examples of this invention; Figure 7 This is a breakthrough curve diagram of the copper adsorption column of the copper adsorption material used in the experimental examples of this invention for treating copper-containing solutions; Figure 8 This is a graph showing the desorption data of copper ions after the adsorption column of the copper adsorption material in the experimental example of this invention has been saturated. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0035] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.

[0036] Example 1 This embodiment provides a method for preparing a copper adsorbent material, specifically including the following steps: S1: 15.2 g of 2-hydroxybenzoyl hydrazide (0.10 mol) and 12.0 mL of methacryloyl chloride (0.10 mol) were mixed and then added to 200 mL of chloroform. After stirring and dissolving, 15.3 mL of triethylamine (0.11 mol) was added, and the mixture was reacted at room temperature for 6 h. During the reaction, a large amount of pale yellow precipitate was formed. After the reaction was complete, the mixture was filtered and washed three times with cold ethanol to obtain the crude product. The crude product was recrystallized in n-hexane and dried under vacuum at 60 °C for 12 h to obtain 28.5 g of salicylhydrazide monomer (denoted as Sh-ma), with a yield of 90.2%. The structural formula of the salicylhydrazide monomer is as follows: Where R1 is H and R2 is CH3. The 1H and 1C NMR spectra of salicylhydrazide monomers are shown below. Figure 1 and Figure 2 As shown.

[0037] according to Figure 1-2 As can be seen, each proton peak in the NMR spectrum has been clearly assigned, and the number of carbon peaks corresponds one-to-one with the number of atoms in the target product, indicating the successful synthesis of salicylhydrazine monomers.

[0038] S2: 10 g of salicylhydrazide monomer (45 mmol), 3.91 g of methacrylic acid (45 mmol), 0.45 g of ethylene glycol dimethacrylate (2.22 mmol), and 0.15 g of azobisisobutyronitrile (0.9 mmol) were mixed and then added to 50 mL of chloroform to form a pre-emulsion. 200 mL of deionized water containing 0.65 g of sodium dodecyl sulfate (2.22 mmol) was added dropwise and stirred for 30 min to form an emulsion. The emulsion was transferred to a three-necked flask, nitrogen was purged for 30 min to remove oxygen, and the temperature was raised to 75 °C. The emulsion polymerization reaction was carried out for 6 h. After the reaction, the mixture was cooled to room temperature, and the product was centrifuged, washed five times successively with deionized water and ethanol, dried under vacuum at 60 °C for 24 h, ground, and sieved to obtain the copper adsorbent material (denoted as pSh-ma (1:1)). The FT-IR structure of the copper adsorbent material is shown below. Figure 3 As shown.

[0039] Example 2 This embodiment provides a method for preparing a copper adsorbent material. The difference between this embodiment and Example 1 is that in S2, 10 g of salicylhydrazine monomer is replaced with 3.33 g, and the molar number of salicylhydrazine monomer is 15 mmol, thus obtaining a copper adsorbent material (denoted as pSh-ma (1:0.33)).

[0040] Example 3 This embodiment provides a method for preparing a copper adsorbent material. Compared to Example 1, the difference lies in S2: 10 g of salicylhydrazine monomer is replaced with 6.67 g, and the molar number of the salicylhydrazine monomer is 30 mmol, thus obtaining the copper adsorbent material (denoted as pSh-ma (1:0.67)). The FT-IR structure of the copper adsorbent material is shown below. Figure 3 As shown.

[0041] according to Figure 3 It can be known that 2902 cm -1 The weak peak at 1723 cm⁻¹ represents the reverse symmetric stretching vibration of the CH group in alkanes, which is evidence of successful polymerization of the alkane backbone; -1 The strong, sharp peak at 1609 cm⁻¹ is a characteristic peak of the carbon group (-C=O) in carboxylic acids. -1 At each point, there is a small peak representing the bending vibration of secondary amine hydrogen (-NH), at 1050 cm⁻¹. -1 The small peaks representing the stretching vibrations of "-CN-" are evidence of successful polymerization of salicylhydrazine monomers.

[0042] Example 4 This embodiment provides a method for preparing a copper adsorbent material. The difference between this embodiment and Example 1 is that in S2, 10 g of salicylhydrazine monomer is replaced with 15 g, and the molar number of salicylhydrazine monomer is 68 mmol, thus obtaining a copper adsorbent material (denoted as pSh-ma (1:1.5)).

[0043] Example 5 This embodiment provides a method for preparing a copper adsorbent material. The difference between this embodiment and Embodiment 1 is that in S1, 2-hydroxybenzoyl hydrazine is replaced with 2-hydroxy-4-morpholinobenzoyl hydrazine, and methacryloyl chloride is replaced with methacrylic anhydride; the molar ratio of 2-hydroxy-4-morpholinobenzoyl hydrazine to methacrylic anhydride is 1:1. The structural formula of the salicylhydrazine monomer is as follows: Where R1 is NC4H8O and R2 is CH3.

[0044] Example 6 This embodiment provides a method for preparing a copper adsorbent material. The difference between this embodiment and Embodiment 1 is that in S1, 2-hydroxybenzoyl hydrazine is replaced with 2-hydroxy-4-diethylaminobenzoyl hydrazine, and methacryloyl chloride is replaced with acryloyl chloride; the molar ratio of 2-hydroxy-4-diethylaminobenzoyl hydrazine to acryloyl chloride is 1:1. The structural formula of the salicylhydrazine monomer is as follows: , where R1 is N(C2H5)2 and R2 is H.

[0045] Comparative Example 1 This comparative example provides a method for preparing an adsorbent material. The difference between this comparative example and Example 1 is that no salicylhydrazine monomer was added in S2, and the resulting adsorbent material is denoted as pSh-ma (1:0).

[0046] Experimental Example 1. The copper adsorbent material prepared in Example 1 was subjected to a metal ion selectivity test. Specific steps included: Li... + Na + K + Mn 2+ Ni 2+ Co 2+ Fe 3+ Al 3+ A 7.8 mmol / L metal ion solution was prepared, and then mixed with a copper-containing solution to obtain a mixed solution. The pH of the mixed solution was adjusted to 6. The copper-containing solution contained Cu. 2+ The concentration was 7.8 mmol / L. 20 mL of the mixture was taken into each conical flask, and 20 mg of copper adsorbent was added. The mixture was shaken at 25℃ for 24 h. The concentrations of each ion before and after adsorption were measured. The ion selectivity of the copper adsorbent is shown in the figure. Figure 4 As shown.

[0047] according to Figure 4 It can be seen that copper adsorbent materials are effective against Cu. 2+ K d The value remained stable at 576-609 mL / g, for Co 2+ The separation factor (α) is 187, and the copper adsorbent material has a high affinity for Ni. 2+ The separation factor (α) is 191.5, indicating that the copper adsorbent material has the ability to selectively separate copper ions.

[0048] 2. Static adsorption tests were performed on the copper adsorbent materials prepared in Examples 1-3 and the adsorbent material prepared in Comparative Example 1. Specific steps: 20 mg of the copper adsorbent material or adsorbent material prepared in Examples 1-3 was added to 20 mL of a copper ion solution with a pH of 5. The copper ion solution contained Cu... 2+ Initial concentrations were 100, 200, 300, 400, and 500 mg / L; the mixture was shaken at 180 rpm for 24 h in a constant-temperature shaker at 25℃. After centrifugation, the supernatant was collected, and the residual Cu was determined using ICP-OES. 2+ Concentration. The isothermal adsorption diagram of the copper adsorbent material is shown below. Figure 5 As shown.

[0049] according to Figure 5It can be seen that the maximum adsorption capacity is: pSh-ma (1:1) (192 mg / g) > pSh-ma (1:0.67) (147 mg / g) > pSh-ma (1:0.33) (101 mg / g) > pSh-ma (1:0) (9.53 mg / g). Clearly, the content of salicylhydrazide monomers is related to Cu. 2+ The adsorption capacity is positively correlated with that of Cu, indicating that salicylhydrazine monomers act as adsorbents in copper adsorbent materials. 2+ The role of coordination and binding. It can also be seen that the adsorbent material prepared in Comparative Example 1 exhibits a strong affinity for Cu. 2+ Its adsorption capacity is extremely low, and it can be essentially considered non-adsorbent. The adsorbent material prepared in Comparative Example 1 was unable to separate copper from the copper-containing solution.

[0050] 3. The copper adsorbent materials prepared in Examples 1-3 were subjected to adsorption kinetic tests. Specific steps included: first preparing Cu... 2+ A 500 mg / L copper nitrate solution was prepared, and 100 mg of the copper adsorbent material prepared in Examples 1-3 was uniformly dispersed into 100 mL of the copper nitrate solution. The solution was then placed in a constant temperature shaking incubator (180 rpm, 25°C), and samples were taken at 1, 2, 5, 10, 20, 40, 60, 90, 120, 150, and 180 min. The samples were filtered through a 0.22 μm organic filter, and the Cu content in each filtrate was measured using an atomic absorption spectrophotometer. 2+ Concentration, adsorption kinetics of copper adsorbent material as shown in the figure Figure 6 As shown.

[0051] according to Figure 6 It can be seen that the copper adsorbent material has a high adsorption capacity for Cu within the first 10 minutes of adsorption. 2+ The adsorption rate has already reached over 90%, and the data can be successfully fitted to the pseudo-second-order kinetic model.

[0052] 4. The copper adsorbent material prepared in Example 1 was subjected to adsorption column treatment of copper-containing solutions for testing. Specific steps: 0.5 g, 0.75 g, and 1.00 g of copper adsorbent material were mixed evenly with 25 mL of quartz sand, and then filled into 30 mL adsorption columns respectively. Pure water was then pumped into the adsorption column at a flow rate of 1 mL / min until the pH of the outlet solution was the same as the pH of the inlet solution. The pure water was then replaced with 1.5 g / L Cu at pH 5. 2+ Solution. The leachate was pumped into the adsorption column at a constant flow rate (1 mL / min) using a peristaltic pump, and samples of the eluent were taken every 5 min until the fixed-bed experiment had been conducted for 150 min. Finally, the sample was filtered through a 0.22 μm organic filter, diluted after filtration, and the Cu content in the sample was detected using an atomic absorption spectrophotometer. 2+Concentration. Breakthrough curve of copper-containing solution treated by adsorption column of copper adsorption material is shown in the figure. Figure 7 As shown.

[0053] according to Figure 7 It can be seen that the penetration point (C) t The adsorption rate (C0 = 0.1) appeared at approximately 60 min, and the dynamic adsorption capacity was found to be 139.76 mg / g using the Thomas model.

[0054] 5. The copper adsorbent material prepared in Example 1 was subjected to desorption testing. 1.00 g of copper adsorbent material was mixed evenly with 25 mL of quartz sand and then packed into 30 mL adsorption columns. Pure water was pumped into the adsorption column at a flow rate of 1 mL / min until the pH of the outlet solution was the same as that of the inlet solution. Then, the pure water was replaced with 1.5 g / L Cu at pH 5. 2+ The solution was added until the adsorption column was saturated. Then, pure water was pumped into the adsorption column at a flow rate of 1 mL / min until the pH of the outlet solution was the same as the inlet solution. The pure water was then replaced with nitric acid solutions of 1 mol / L and 0.5 mol / L. The leachate was pumped into the adsorption column at a constant flow rate (2 mL / min) using a peristaltic pump, and samples of the effluent were taken every 5 min until the desorption experiment had been performed for 60 min. Finally, the sample was filtered through a 0.22 μm organic filter, diluted, and the Cu content in the sample was detected using an atomic absorption spectrophotometer. 2+ Concentration. The desorption data of copper ions after the adsorption column is saturated is shown in the graph. Figure 8 As shown.

[0055] according to Figure 8 It can be seen that the desorption curves of both concentrations of nitric acid show a "rapid rise-peak-rapid fall-level trend". The adsorption capacities at the two acid concentrations are similar (about 164 mg), but the desorption capacity of 0.1 mol / L HNO3 is 151.041 mg, with a desorption rate of 91.8%; the desorption capacity of 0.05 mol / L HNO3 is 139.274 mg, with a desorption rate of 84.6%.

[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A copper adsorbent material, characterized in that, Copper adsorbent materials were prepared by emulsion polymerization of salicylhydrazine monomers and methacrylic acid; the structural formula of the salicylhydrazine monomers is as follows: R1 is one of H, N(C2H5)2, or NC4H8O, and R2 is H or CH3.

2. The copper adsorbent material according to claim 1, characterized in that, The molar ratio of methacrylic acid to salicylhydrazine monomers is 1:0.33~1.

5.

3. A method for preparing a copper adsorbent material as described in claim 1 or 2, characterized in that, Includes the following steps: S1 involves mixing salicylhydrazide compounds with propylene compounds, dissolving them in chloroform, and then reacting them with a catalyst to obtain salicylhydrazide monomers. S2 involves adding salicylhydrazine monomers, methacrylic acid, crosslinking agent, and initiator to chloroform and stirring until homogeneous to form a pre-emulsion. Water containing emulsifier is then added to the pre-emulsion and stirred to form an emulsion. After deoxygenation of the emulsion, a copper adsorbent material is obtained.

4. The method for preparing the copper adsorbent material according to claim 3, characterized in that, Salicylhydrazide compounds include one or more of 2-hydroxybenzoylhydrazide, 2-hydroxy-4-diethylaminobenzoylhydrazide, and 2-hydroxy-4-morpholinobenzoylhydrazide.

5. The method for preparing the copper adsorbent material according to claim 3, characterized in that, Propylene compounds include one or more of methacryloyl chloride, methacrylic anhydride, acryloyl chloride, and acrylic anhydride.

6. The method for preparing the copper adsorbent material according to claim 3, characterized in that, The molar ratio of salicylhydrazide compounds to propylene compounds is 1:0.9~1.

2.

7. The method for preparing the copper adsorbent material according to claim 3, characterized in that, The crosslinking agent is ethylene glycol dimethacrylate, which is 0.5 to 5% of the molar amount of salicylhydrazine monomer.

8. The method for preparing the copper adsorbent material according to claim 3, characterized in that, The emulsifier is sodium dodecyl sulfate, which is 1 to 5% of the molar amount of salicylhydrazine monomer.

9. The method for preparing the copper adsorbent material according to claim 3, characterized in that, The initiator is azobisisobutyronitrile, which is 0.2 to 2% of the molar amount of salicylhydrazine monomer.

10. The application of a copper adsorbent material in copper-containing wastewater, characterized in that, The copper adsorbent material is prepared by the method described in claim 1 or 2 or any one of claims 3-9.